Curdlan Limits Mycobacterium tuberculosis Survival Through STAT-1 Regulated Nitric Oxide Production - Negi, Shikha; Pahari, Susanta; Das, Deepjyoti Kumar; Khan, Nargis; Agrewala, Javed N. (Frontiers in Microbiology, 2019)
Host-directed therapies have emerged as an innovative and promising approach in tuberculosis (TB) treatment due to the observed limitations of current TB regimen such as lengthy duration and emergence of drug resistance. Thus, we explored the role of curdlan as a novel strategy to activate macrophages by boosting their innate immune response against Mycobacterium tuberculosis (Mtb). The aim of the study was to investigate the role of curdlan in restricting the Mtb growth both in vitro and in vivo. Further, the immunomodulatory potential of curdlan (beta glucan polysaccharide) against Mtb and the underlying mechanism is largely unknown. We found that curdlan treatment enhanced the antigen presentation, pro-inflammatory cytokines, Mtb uptake and killing activity of macrophages. In vivo studies showed that curdlan therapy significantly reduced the Mtb burden in lung and spleen of mice. Administration of curdlan triggered the protective Th1 and Th17 immunity while boosting the central and effector memory response in Mtb infected mice. Curdlan mediated anti-Mtb activity is through signal transducer and activator of transcription-1 (STAT-1), which regulates nitric oxide (NO) production through inducible NO synthase (iNOS) induction; along with this activation of nuclear factor kappa B (NF-ĸB) was also evident in Mtb infected macrophages upon curdlan stimulation. Thus, we demonstrate that curdlan exerts effective anti-tuberculous activity to be used as a potential host-directed therapy against Mtb.